ANTARYAMIN: THE INNER SPIRIT: . - Thottakara, Augustine (Journal of Dharma, 1998)
Upanisadic literature [800-300 BeE] is very often characterized as a powerful expression of revolt against and a refusal of .Brahmanic ritualism. It, in no uncertain terms, condemned the stereotyped, and very often meaningless, rituals and sacrifices, and loudly proclaimed that the ultimate liberation from embodied existence cannot be realized through these external expressions of religiosity and spirituality. Instead, it championed the intuitive, experiential and mystical knowledge of Brahman, which is the ultimate cause of everything, the unifying force of the universe and the supreme goal of all lives, as the only and sure means to break the inexorable cycle of births, deaths and rebirths.